PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN: PENDEKATAN DENGAN METODE STRUCTURAL EQUATION MODEL PADA PERUSAHAAN YANG TERDAFTAR DI BEI - ASARIWANGI, VERNI; ., YUDIANA (MONETER, 2013)
The objective of this study is to examine the influence of corporate governance index (board of director, board of commissioners, committee audit and information content) to firm performance of 73 Indonesian listed companies in 2009. MTobin’s Q as firm performance measure, with the control variables are size, debt and industry. This study by simultaneous equation approach using structural equation modeling. This research based on Zuraidah’s & Norman’s (2005) suggestion there is probability relationship between firm performance and corporate governance is simultaneously. The results obtained in all econometric approach show a positive and significant influence of firm performance related to corporate governance. The results of this study are consistent with studies by Black (2001), Black et al. (2006), Durnev and Kim (2005), Bai et al. (2003), Beiner et al. (2004) and Brown and Caylor (2004), which also used corporate governance index and found a significant positive relation between firm value and corporate governance. The result show a negative and not significant about the relationships of corporate governance to firm performance. Moreover, results by simultaneous equation approach indicate a relation of reverse causality between corporate governance index and firm performance.